2001
DOI: 10.1088/0960-1317/11/4/325
|View full text |Cite
|
Sign up to set email alerts
|

Innovative design and modelling of a micromechanical relay with electrostatic actuation

Abstract: The behaviour of a surface-micromachined electrostatic microrelay and the influence of the design parameters on the pull-in voltage and the contact force are analysed by means of finite-element method simulations. Three models have been used and compared-a fully three-dimensional coupled electromechanical numerical simulation using CoSolveEM, a two-dimensional coupled simulation, and a simplified semi-analytical model based on the parallel-plate capacitor approximation-and these have shown good conformity. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…It is therefore required implementing effective numerical models to predict the electromechanical behaviour of microstructures actuated by the electric field, as stand-alone systems or as structural components of assembled microdevices. Electromechanical coupling makes this prediction rather difficult, because of the interaction between electrical and mechanical domains, thus requiring a coupled-field analysis, which includes some nonlinearities [14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore required implementing effective numerical models to predict the electromechanical behaviour of microstructures actuated by the electric field, as stand-alone systems or as structural components of assembled microdevices. Electromechanical coupling makes this prediction rather difficult, because of the interaction between electrical and mechanical domains, thus requiring a coupled-field analysis, which includes some nonlinearities [14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…They found that in order to the lateral deflection is strongly FIGURE 4.31. The effect of stress gradient on the contact force of a RF switch [201].…”
Section: Residual Stress Gradient Characterizationmentioning
confidence: 99%
“…In order to obtain accurate prediction, 3D FEM analyses are usually used associated with experimental data. Sattler et al [201] investigated the influence of the existence of residual stress gradient to a RF MEMS switch using CoSolve module of MEMCAD [202]. The initial curvature caused by the stress gradient would effectively change the contact force of the switch.…”
Section: Residual Stress Gradient Characterizationmentioning
confidence: 99%
“…where L is the length of the cantilever, and B is the peak-to-valley bow [39]. In order to analyze the beams, the stress states before release, directly after release, and after the beams bend must be taken into consideration.…”
Section: Beam Theory: Cantilever Beamsmentioning
confidence: 99%